Pengaruh layanan konseling kelompok dengan teknik token economy untuk meningkatkan motivasi belajar siswa - Wulansari, Siska Devi; Purwati, Purwati; Indiati, Indiati (Borobudur Counseling Review, 2021)
This study purposes to determine the effect of group counseling services with token economy techniques to increase student learning motivation. The method of data collection is done by using a learning motivation questionnaire. The validity test of the learning motivation questionnaire instrument used the product moment formula while the reliability test used the Cronbach alpha formula with the help of SPSS for Windows version 23.0. The analysis prerequisite test consists of a normality test and a homogeneity test. Data analysis used parametric statistical techniques, namely the Paired Sample T-Test test with the help of the SPSS for Windows version 20.0 program. The results showed that group counseling with the token economy technique had an effect on increasing students' learning motivation. This is evidenced from the results of the analysis of the Paired Sample T-Test on those who were treated with a probability value of sig (2 – tailed) 0.000 <0.05. Based on the results of the analysis and discussion, there is a difference in the average score of the student learning motivation questionnaire before and after treatment on students by 27.34%. The results of the study can be concluded that group counseling with the token economy technique can increase students' learning motivation. Keywords: group counseling, learning motivation, token economy.